Psycho-social perspectives on mental health and well-being - Padmanaban, Srinivasan, 1971-; Subudhi, Chittaranjan, 1989- (Advances in psychology, mental health, and behavioral studies., 2020)
"This book examines the physical, social, and emotional aspects of mental health and well-being"--Provided by publisher.